Theoretical Prediction and Thermal Transport Properties of Novel Monolayer TlPt2Se3. Issue 5 (23rd February 2022) - Nair, Surabhi Suresh; Sajjad, Muhammad; Singh, Nirpendra
Abstract: The theoretical prediction, electronic properties, and thermal transport properties of novel monolayer TlPt2 Se3 are investigated using the first‐principles calculations and semi‐classical Boltzmann transport theory. The calculated phonon band structure and exfoliation energy confirm that monolayer TlPt2 Se3 is a stable material and can be exfoliated from its bulk counterpart. The exfoliation energy of the monolayer turns out to be 37 meV Å −2, comparable with the exfoliation energy of monolayer PdSe2 . The HSE06 indirect bandgap of monolayer (bulk) TlPt2 Se3 amounts to 1.18 eV (0.63 eV). The relaxation time is calculated considering three types of scattering mechanisms. The monolayer outperforms the bulk counterpart in the Seebeck coefficient and power factor for both p ‐type and n ‐type dopings. Monolayer TlPt2 Se3 shows a high p ‐type Seebeck coefficient of 211 µV K −1 compared to the n ‐type Seebeck coefficient of 103 µV K −1 at maximum considered temperature (600 K) and a carrier concentration (10 20 cm −3 ). The calculated lattice thermal conductivity of monolayer TlPt2 Se3 is 1.92 W m −1 K −1 at 600 K which is lower than the monolayer PtSe2 and MoSe2 . The p ‐type figure of merit of 0.64 (at 600 K) affirms that the monolayer TlPt2 Se3 is an excellent thermoelectric material. Abstract : Thermoelectric devices are helpful for the conversion of waste heat into electricity and are, therefore, technologically important. The first‐principles calculations show that the TlPt2 Se3 monolayer outperforms the bulk counterpart. The low lattice thermal conductivity of 1.92 W m −1  K −1 and high p‐type power factor of 3.90 × 10 –3 W m −1  K −2 result in a figure of merit of 0.64 at 600 K.